Germinação e desenvolvimento inicial de Enterolobium gummiferum (mart.) J. F. Macbr. (Fabaceae) - SILVA, Whalleff Pereira da (Universidade Federal do Tocantins, 2023)
Enterolobium gummiferum (Mart.) J. F. Macbr. (Fabaceae) is a Cerrado species whose seeds are physically dormant. In recent years there has been a considerable decrease in the populations of this species in Tocantins. Thus, the objective of this work was to study the germination and initial development of this species. The influence of mechanical scarification (uni and bilateral) on seed germination was evaluated. The description of the hypocotyl-radicle axis, epicotyl, cotyledon, eophilus, along the formation of the seedling, was performed. The effect of four storage periods (6, 12, 18 and 24 months) and different temperatures (25, 30 and 35oC) on the germination process was also verified, as well as the influence of different light levels (0, 50 and 75% retention of solar radiation) on the initial development of seedlings. The results of germination were evaluated by germinability (G), mean germination time (MTG), and synchronization index (SI) and those about luminosity by the following variables: photosynthetic pigment contents, number of leaves, and absolute growth rates in stem diameter and height (TCAA and TCDC). The non-scarified seeds (control) did not germinate. There was no significant difference between uni- and bilateral scarifications concerning the variables analyzed, although germinability was higher in unilaterally scarified seeds. The germination of E. gummiferum seeds is epiphygeal and phanerocotyledonary with the hypocotyl-radicle axis broad at the base and narrow at the end; the root is axial; the cotyledons are persistent and the eophiliums are recomposed. Regarding the storage periods and the effect of temperature on the germination process, no significant differences were found for G and IS. The TMG decreased throughout the storage period. In regarding the influence of the luminosity levels on the development it was verified that the increase of shading caused an increase in TCAA and a decrease in TCDC. No significant variations were observed in relation to the number of leaves. The highest values for photosynthetic pigments were detected at 50% shading with a reduction at higher levels. These results corroborate the fact that E. gummiferum is a climactic species, that is, more adapted to shaded environments, but with relative availability of light.